2016
DOI: 10.1007/s13277-016-5122-y
|View full text |Cite
|
Sign up to set email alerts
|

The C-reactive protein/albumin ratio predicts overall survival of patients with advanced pancreatic cancer

Abstract: Recent studies have demonstrated the prognostic value of the C-reactive protein/albumin (CRP/Alb) ratio in cancer. However, the role of the CRP/Alb ratio in advanced pancreatic cancer (PC) has not been examined. A retrospective study of 233 patients with advanced PC was conducted. We investigated the relationship between the CRP/Alb ratio, clinicopathological variables, and overall survival (OS). The optimal cutoff point of the CRP/Alb ratio was 0.54. A higher CRP/Alb ratio was significantly associated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 34 publications
6
91
3
Order By: Relevance
“…Pancreatic cancers of the body and tail were found to have lower rates of survival . However, in Liu et al and Wu et al’s study, no statistically significant relationship was found between tumor location and OS . In this study, with the univariate analysis, cancerization at head of pancreas was statistically significantly associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 51%
“…Pancreatic cancers of the body and tail were found to have lower rates of survival . However, in Liu et al and Wu et al’s study, no statistically significant relationship was found between tumor location and OS . In this study, with the univariate analysis, cancerization at head of pancreas was statistically significantly associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 51%
“…The GPS was recently studied as a predictive factor for response to a novel therapeutic in advanced PC . Recent studies have also suggested that CRP:Albumin ratio and neutrophil:lymphocyte ratio also have prognostic validity . In routine practice, this score could help identify patients at high risk for PAWL and cachexia and could promote early intervention.…”
Section: Assessment Of Pawlmentioning
confidence: 99%
“…In many studies, these values are combined into calculated inflammatory variables (NLR, PLR, and CRP-albumin ratio). These variables have been validated as prognostic markers [12][13][14][15]. Based on results of the present study, these calculated variables (NLR, PLR, and CRP-albumin ratio) were found to be more predictive than other markers of inflammation.…”
Section: Discussionmentioning
confidence: 59%
“…Therapeutic strategies considering proper prognostic markers could help clinicians bypass worthless toxicities of aggressive therapies. Recently, various inflammatory markers have been validated as prognostic indicators in many cancers including PC [12][13][14][15]. However, few studies have systematically evaluated these markers.…”
Section: Discussionmentioning
confidence: 99%